1980
DOI: 10.1111/j.1365-2125.1980.tb01756.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated investigations of cyclophosphamide disposition in myeloma patients receiving intermittent chemotherapy.

Abstract: 1 The disposition of cyclophosphamide was investigated in a group of myeloma patients. 2 Marked changes in clearance and volume of distribution of cyclophosphamide occurred between investigations. 3 The observed changes in disposition did not correlate with biochemical estimates of renal and hepatic function or plasma protein status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…However, Bramwell et al found such wide individual variations in cyclophosphamide break-down that they could not establish a correlation between cyclophosphamide or alkylating metabolites and renal insufficiency. 3,4 They also showed that further metabolism before renal elimination was an important route of removal of alkylating activity. Grochow et al reviewed the clinical course of 120 myeloma patients receiving 60 mg/kg of CPA and failed to find any difference in hematologic toxicity between patients with normal and abnormal renal function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Bramwell et al found such wide individual variations in cyclophosphamide break-down that they could not establish a correlation between cyclophosphamide or alkylating metabolites and renal insufficiency. 3,4 They also showed that further metabolism before renal elimination was an important route of removal of alkylating activity. Grochow et al reviewed the clinical course of 120 myeloma patients receiving 60 mg/kg of CPA and failed to find any difference in hematologic toxicity between patients with normal and abnormal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…However, little information is available about the pharmacokinetics of CPA in renal insufficiency. Bramwell et al reported that the alkylating activity of CPA is influenced more by the wide individual variation in CPA breakdown than by decreased renal function 3,4 and Grochow et al 5 failed to show any correlation between the severity of renal insufficiency and hematopoietic toxicity. Therefore, adjusting CPA doses in the presence of renal insufficiency has not been recommended.…”
mentioning
confidence: 99%
“…Its metabolites are more highly protein bound, but none more than 67%. The calculated volume of distribution (V d) approximates total body water and has ranged from 0.54 to 1.1 L/kg in studies in humans (Edwards et al 1980;Grochow & Colvin 1983). In patients with multiple sclerosis treated with daily oral cyclophosphamide the concentrations in plasma and cerebrospinal fluid (CSF) were similar (Hommes et al 1983); patients with brain tumours receiving the drug intravenously exhibited peak CSF concentrations which were 50% of those in plasma.…”
Section: Distributionmentioning
confidence: 99%
“…Plasma halflife decreases with subsequent doses at both low (D'Incalci et al 1979) and high dose levels (Graham et al 1983;Sladek et al 1980) and the peak levels of alkylating activity in plasma also increased over a course (Bagley et al 1973). Edwards et al (1980) did not observe the same decrease in half-life but they did find an increase in clearance. In another study no change in pharmacokinetic parameters was noted after a 22-day course of low dose daily cyclophosphamide (Mouridsen et al 1976).…”
Section: Biotransformationmentioning
confidence: 47%